2022
DOI: 10.1002/fsn3.2851
|View full text |Cite
|
Sign up to set email alerts
|

Influence of guar gum and chitosan enriched with lemon peel essential oil coatings on the quality of pears

Abstract: Pear is a typically climacteric fruit and highly perishable with a low shelf life owing to extreme metabolic activity after harvesting. The present study aimed to reduce weight loss and improve the firmness of pear during storage. The lemon peel essential oil (LPEO) has gained considerable attention due to being the richest source of bioactive compounds that behaved as a natural antioxidant agent, being cost‐effective, and being generally recognized as safe. Edible coatings equipped with a natural antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…60 demonstrated that chitosan coatings enhanced with LPEO exhibited significantly higher antioxidant activity in comparison to the control group without EOs. Iftikhar et al 61 confirmed the positive impact on the antioxidant activity of pear when treated with LPEO as compared to untreated pear over the storage period.…”
Section: Essential Oils Based On Different Food Wastementioning
confidence: 89%
See 3 more Smart Citations
“…60 demonstrated that chitosan coatings enhanced with LPEO exhibited significantly higher antioxidant activity in comparison to the control group without EOs. Iftikhar et al 61 confirmed the positive impact on the antioxidant activity of pear when treated with LPEO as compared to untreated pear over the storage period.…”
Section: Essential Oils Based On Different Food Wastementioning
confidence: 89%
“…demonstrated that chitosan coatings enhanced with LPEO exhibited significantly higher antioxidant activity in comparison to the control group without EOs. Iftikhar et al 61 confirmed the positive impact on the antioxidant activity of pear when treated with LPEO as compared to untreated pear over the storage period. The results indicated that in treatments involving LPEO in the coating, the antioxidant capacity of the coated pear remained more stable throughout the storage period.…”
Section: Essential Oils Based On Different Food Wastementioning
confidence: 91%
See 2 more Smart Citations
“…However, these films possess certain limitations such as toxicological effects, costly environmental issues, poor mechanical attributes, high water affinity, and others ( 21 , 22 ). On the other hand, using antimicrobial materials from natural sources is among emerging research topics in preserving food from microbial contaminations and developing anti-microbial food packaging with numerous advantages ( 23 , 24 ). For example, reinforcement of SBFs with natural fillers having biocompatible and biodegradable valuable nature in medicine, drug release, packaging, and agricultural research ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%